Human Resource Management and Innovative Performance in Non-profit Hospitals: The Mediating Effect of Organizational Culture - Acosta-Prado, Julio C.; López-Montoya, Oscar H.; Sanchís-Pedregosa, Carlos; Zárate-Torres, Rodrigo A. (Frontiers in Psychology, 2020)
Literature suggests that human resources of non-profit hospitals (NPHs) present features that could potentially reach any expected organizational performance even when the attention to human resource management (HRM) is often low in non-profit organizations. Nowadays, ambitious organizations strive to obtain a profitable performance that is also innovating and do it through building an organizational culture (OC). In contrast, for NPHs a positive culture is given by their human resources traits. However, there is not enough literature to understand how these three variables behave together. This study aims to explain the influence of HRM on Innovative Performance (IP) mediated by OC. The research model was assessed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The results support all the stated hypotheses. Both, HRM and OC are moderately strong predictors of IP, and OC mediates partially and in a complementary way, the relationship between HRM on IP. An importance-performance map analysis (IPMA) was performed to expand the PLS-SEM results. The OC indicators show greater importance to explain IP. Consequently, they are the most relevant indicators to initiate management actions by NPHs. The influence of HRM on IP represents an opportunity for NPH as it implies an affordable investment in comparison to the cost of technological solutions for enterprises.